2008
DOI: 10.1021/nl801012r
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Induced, Superhydrophobic to Superhydrophilic Switching in Multiwalled Carbon Nanotube Papers

Abstract: Superhydrophobic multiwalled carbon nanotube bucky paper, fabricated after ozonolysis, shows fascinating electrowetting behavior, which could be remarkably tuned by changing key solution variables like the ionic strength, the nature of the electrolyte, and the pH of the water droplet. More significantly, the droplet behavior can be reversibly switched between superhydrophobic, Cassie-Baxter state to hydrophilic, Wenzel state by the application of an electric field, especially below a threshold value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 19 publications
2
92
0
Order By: Relevance
“…Up to now, there are only some reports in the literatures about the electrowetting on superhydrophobic surfaces [149][150][151][152][153][154][155][156][157][158][159][160][161][162]. Krupenkin et al [154] demonstrated for the first time a method for dynamic electrical control over the wetting behavior of liquid droplets on superhydrophobic nanostructured surfaces by etching microscopic array of cylindrical nanoposts into the surface of a silicon wafer, finding that the wetting properties of the surface can be tuned from superhydrophobic behavior to nearly complete wetting as a function of applied voltage and liquid surface tension, with no reversible effect (Fig.…”
Section: Electrowettingmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, there are only some reports in the literatures about the electrowetting on superhydrophobic surfaces [149][150][151][152][153][154][155][156][157][158][159][160][161][162]. Krupenkin et al [154] demonstrated for the first time a method for dynamic electrical control over the wetting behavior of liquid droplets on superhydrophobic nanostructured surfaces by etching microscopic array of cylindrical nanoposts into the surface of a silicon wafer, finding that the wetting properties of the surface can be tuned from superhydrophobic behavior to nearly complete wetting as a function of applied voltage and liquid surface tension, with no reversible effect (Fig.…”
Section: Electrowettingmentioning
confidence: 99%
“…Anti-icing [138,13,[139][140][141][142] Super oil-repellent [143][144][145][146][147][148] Electrowetting [149][150][151][152][153][154][155][156][157][158][159][160][161][162] Responsive superhydrophobic surfaces [163,164,7,[165][166][167][168] Water droplet evaporation and condensation [169][170][171][172][173][174][175][176][177][178][179] Sticky and superhydrophobicity [180][181][182][183][184]…”
Section: Applicationsmentioning
confidence: 99%
“…Various investigations have been conducted to examine the motion of a liquid droplet on a solid surface using external fi elds such as gravity, heat gradients [65,66], electric fi elds [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81], magnetic fi elds [82], photo-illumination [83], blowing wind [84] and vibration [85].…”
Section: Control Of Water Droplets On Solid Surfacesmentioning
confidence: 99%
“…A hydrophobic solid surface generally becomes hydrophilic upon application of an electric fi eld [67,68]. Electrowetting is a microfl uidic phenomenon that has grown explosively as a driving mechanism for various fl uidic and electro-optic applications [69][70][71][72][73].…”
Section: Control Of Water Droplets On Solid Surfacesmentioning
confidence: 99%
“…Superhydrophobic surfaces have been applied in MEMS field especially in electrowetting research. Kakade et al [2] fabricated superhydrophobic multiwalled carbon nanotube bucky paper showing fascinating electrowetting behavior. The droplet behavior can be reversibly switched between superhydrophobic Cassie-Baxter state to hydrophilic Wenzel state by the application of an electric field, especially below a threshold value.…”
Section: Introductionmentioning
confidence: 99%